Formação de leitores e cidadania na Biblioteca Pública Municipal Avertano Rocha do Município de Belém do Pará - SANTOS, Paulo Skip Sodré dos (2017)
This study aims to verify if the training of readers in the Avertano Rocha Public Library, in the city of Belém do Pará, is efficient, making readers aware of the population assisted, both in the library environment and outside it, in their daily lives. The specific objectives are: to verify how the reader training process takes place in the Avertano Rocha Library, Identify the position of the users about the importance of the Avertano Library for their reading training and to know the position of the librarian about the formation of readers in the library. The methodology adopted for this study was a bibliographical research to theoretically base the research and the field research was of the quanti-qualitative type, and the tools adopted to obtain the data were questionnaires and interviews applied to the librarian and to the users, besides request Of projects that are developed in the institution. It was found that in BPMAR there is a training of readers, but with projects aimed mainly at the young students of the district of Icoaraci to the detriment of other social segments for which there are projects, but that are not sufficient or adequate to attract significant amount of users Adults and seniors to the Library.